Metabolite footprinting and fingerprinting in Saccharomyces cerevisiae - Aygök, Ali Erdem. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The metabolic response of S. cerevisiae cells of galactose metabolic pathway genes, hexose transporter genes, transcription regulation and respiration related genes were investigated. Homozygous deletion mutants rgt1Δ/ rgt1Δ, adh6Δ/ adh6Δ, gal4Δ/ gal4Δ, gal6Δ/ gal6Δ, gal7Δ/ gal7, gal80Δ/ gal80Δ, hap4Δ/ hap4Δ, hxt10Δ/hxt10Δ, hxt12Δ/ hxt12Δ, mba1Δ/ mba1Δ, mig1Δ/ mig1Δ, snf3Δ/ snf3Δ, yel057cΔ/yel057cΔ, and hoD/hoD (reference strain) were grown in batch reactors which were containing 20 gL-1 initial glucose in minimal medium. The samples were collected at statinaory phase of fermentation analysed for extracellular (metabolic footprinting) and intracellular (metabolic fingerprinting) metabolome profiles by Q-TOF mass spectrometer. Then, metabolic data were processed by PCA and ICA methods to identify the clusters within the biologically or functionally related deletion mutants. Pearson correlation analysis was applied to metabolic data, which shows the interaction between the deletion mutants. The results of correlation analysis confirmed the accuracy of PCA and ICA. Signatures of deletion mutants at certain m/z values were obtained for extracellular and intracellular metabolome data. Then, these m/z values were used for pair-wise mutant correlations. In conclusion, extracellular metabolome data of S. cerevisiae at 20th hour of fermentation, and intracellular metabolome data at 25th hour of fermentation provide better discrimination of known genes. It was also observed that yel057cD deletion mutant (unknown function or relation) appeared in the same region with snf3Δ, adh6Δ, and hxt12Δ. It could be stated that yel057cΔ would play a role in glucose or hexose transport like snf3Δ and hxt12Δ.
Keywords: Saccharomyces cerevisiae -- Metabolism.; Yeast.; Metabolites.